'A dynamic attitude of the gaze': Gabriele Basilico's sense of vertical space. Issue 8 (17th November 2019) - Deriu, Davide
Abstract : High-rise architecture has provided a popular vantage point for urban photographers since the turn of the millennium. Amidst the diffusion of aerial imagery obtained from airborne cameras, the embodied view from above has witnessed a parallel revival. This mode of representation harks back to the early twentieth century when the modern city became a field of exploration for avant-garde photographers in pursuit of a 'new vision', as epitomised by Aleksander Rodchenko's radical high-angle shots which captured Moscow's spatial patterns from uncustomary perspectives. Eight decades later, the Italian photographer Gabriele Basilico revisited the Russian capital and produced a photobook Vertiginous Moscow (2008), that referenced Rodchenko's work. Basilico embraced the vue en plongée to depict the city of and from the Seven Sisters, the monumental towers built under Stalin after World War II. Multiple layers that constitute Vertiginous Moscow are unpacked here with a focus on the photographer's sense of verticality, which he succinctly described as 'a dynamic attitude of the gaze'. This attitude was not limited to the depiction of urban spaces from high vantage points but engaged a broader set of temporal relations with the city's past — as well as intimations of possible futures.